Educational Posters as A Solution to Prevent Bullying in Elementary School: A Qualitative Study on PJBL-Based Civics Learning - Vahita Alfiani; Deni Adi Putra; Holy Ichda Wahyuni (Global Action and Education for Society, 2026)
This study aims to analyze the use of poster media with the Canva platform in bullying prevention education for elementary school students in the subject of Civics with the PJBL approach. Through this analysis, it is hoped that more innovative and interesting ways can be found to increase students' awareness of the importance of bullying prevention, as well as make a positive contribution to character formation and a safe and inclusive learning environment. This research is a qualitative study. The qualitative approach aims to gain an in-depth understanding of reality or phenomena through an inductive thinking process. data was collected through several techniques, namely observation, interviews and documentation. Data analysis in this study used descriptive research analysis according to Miles & Huberman, the analysis consists of three streams of activities that occur simultaneously, namely: data collection, data reduction, data presentation, drawing conclusions/verification. The results of the study showed that the use of poster media using the Canva platform in bullying prevention education carried out at SDN Wonokusumo 1 Surabaya ran smoothly and pleasantly, this shows that Canva facilitates the creation of attractive and informative posters. The conclusion of the analysis of the use of poster media for bullying prevention education for elementary school students in PKN subjects with the Project-Based Learning (PJBL) model shows that poster media is the right tool in increasing student awareness of bullying issues. Well-designed posters can convey clear and attractive messages, making it easier for students to understand various forms of bullying and how to prevent them